(3ebGdI aj GdQO Ydi GdeLHQIs - (3YHO GdLHGQ Hf CMeO GdgePGfj GdGSJQGHGOj,J (B415 (3g` s ((3YHO Gddg Hf fhQ GdOjf Hf YHO Gddg GdMSjfi GdehShi s)
(3ChdgG (B:s
(3PcQJ Cf GdeLHQg bO ELJQGJ ai hbJfG gPG Ydi GdJRGe CTjGA cGf Sdage jeJfYhf ef GdJRGegG s
(3BNQgG (B:s
(3Ydi eG YKQhG Ydjg ai gPg GdQSGdI hZjQgG ef GdgahGJ YUefG Gddg hEjGge Yf GdRdd hhabfG LejYkG ddYde hGdYed s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B_ (3GdfLa (B(182 /3) s
Keywords: (3GdJhMjO hGdedd hGdfMds